Measuring the importance of labor market networks - Judith K. Hellerstein; Melissa McInerney; David Neumark (Institute for the Study of Labor (IZA), 2008)
We specify and implement a test for the importance of network effects in determining the establishments at which people work, using recently-constructed matched employer-employee data at the establishment level. We explicitly measure the importance of network effects for groups broken out by race, ethnicity, and various measures of skill, for networks generated by residential proximity. The evidence indicates that labor market networks play an important role in hiring, more so for minorities and the less-skilled, especially among Hispanics, and that labor market networks appear to be race-based.
urn:nbn:de:101:1-20081114134
Keywords: J15; 330; Networks; race; ethnicity; immigrants; Arbeitsmarkt; Netzwerk; Beschäftigung; Personalbeschaffung; Ethnische Gruppe; Ungelernte Arbeitskräfte; USA